Morality & contemporary warfare - Johnson, James Turner (Yale University Press, 1999)
"When is the use of military force by a nation morally justified? Why has the long accepted moral requirement to protect civilians from intentional attack eroded in recent years? How can the tendency toward unrestrained warfare between parties with major cultural differences be controlled? In this book, James Turner Johnson refocuses the moral analysis of war on the real problems of today's armed conflicts. Moral debates about nuclear war and annihilation fail to address the problems of actual contemporary uses of military force, Johnson argues. We must address the type of armed conflict that has emerged at the end of the twentieth century: local wars - often inflamed by historical, ethnic, or religious animosities and usually fought with conventional weapons that can be carried by individual fighters."--Jacket